Managing Planned Change in an Organization: Overcoming Employee Resistance to Change (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“The environment of business consists of those entire external things which it is exposed and by which it may be influenced, directly or indirectly.” There is symbolic relation between business and the environmental factors. All environmental factors are dynamic which affects the business. So the policies and strategies are made while keeping the change in business environment because changes are necessary for survival, growth of the business. But this change is resist by the employees of the organization because they do not want to cope with new challenges. So is the duty of the manager that he adopt new policies while keeping the resistance of the employees so that the changes made by the business can be applied peacefully in an organization so that it can be successful.